Simalungun Batak Family Support for Elderly Independence - Haloho, Elsa Dora; Bukit, Evi Karota; Tarigan, Mula (Jurnal Kesehatan, 2024)
Aging is an event that will be experienced by everyone who is blessed with a long life. Biologically, elderly people experience a continuous aging process characterized by decreased physical resistance to disease. These various changes often cause elderly people to experience problems in facing life, so family support is needed. This study aims to analyze the influence of Simalungun Batak family support on the independence of the elderly in the working area of the Haranggaol Community Health Center. Type of quantitative research with a cross-sectional approach. The subjects were 149 elderly people who lived at home with family members in Harangaol who were selected using purposive sampling. The instrument was adopted and modified from existing family support, and elderly independence questionnaires and validity and reliability tests were carried out on 30 subjects with r-table >.361, with Cronbach's alpha reliability of .761. The results of the univariate analysis show that the majority of emotional family support is in the excellent category 68 (46%), the appreciation family support is good 63 (43%), the informational family support is sufficient 100 (67%) the instrumental family support is good 75 (50%), the total independence of the elderly is 96 (65%). The Pearson product-moment analysis results show a significant relationship between emotional, appreciative, informational, and instrumental family support and the independence of the elderly. There is a significant relationship between emotional family support, appreciation family support, informational family support, and instrumental family support for the independence of the elderly at the Haranggaol Health Center. It is recommended that the family support the elderly in participating in integrated services, elderly activities, and customary activities to maintain the elderly's level of independence in fulfilling daily living activities.